BIOEQUIVALENCE STUDY OF TRAMADOL + PARACETAMOL (37.5 + 325 MG) IN HEALTHY HUMAN VOLUNTEERS IN FASTING CONDITION (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
The bioequivalence between test and reference Tramadol and Paracetamol (37.5 + 325 mg) tablets was determined in 36 healthy subjects after a single dose in a randomized crossover study under fasting condition. Plasma concentrations were monitored over a period of 24 hour after the drug administration by validated LC/MS/MS analytical method. The pharmacokinetic parameters Cmax, AUC0-t, AUC0-∞, AUC0-t / AUC0-∞, Tmax, Kel and t½ were determined from plasma concentration time profile of both formulations and found to be acceptable. The calculated pharmacokinetic parameters were compared statistically to evaluate bioequivalence between the test and reference products. The analysis of variance did not show any significant difference between the two formulations and 90 % confidence intervals for the ratio of Cmax (92.29 -104.18 %), AUC0-t (99.52 - 104.11 %) and AUC0-∞ (99.05 - 104.22 %) for tramadol and Cmax (93.56 - 110.27 %), AUC0-t (96.37 - 102.70 %) and AUC0-∞ (97.22-103.28 %) for paracetamol test and reference products were within the 80 – 125 % interval, satisfying the bioequivalence criteria the US Food and Drug Administration Guidelines. These results indicate that the test and the reference products of Tramadol and Paracetamol are bioequivalent.